Preparing U.S. Medical Students to Respond to Climate Change - Keanan McGonigle; Frances Gill (Social Medicine Publication Group, 2021)
The devastating hurricane season this year has brought the economic and health impacts of a changing global climate into stark relief. The varied health impacts of climate change can no longer be ignored by anyone who practices medicine - whether primary care or specialist. Physicians are already at the forefront of the response to climate change, advocating on behalf of their patients. Through professional organizations, membership groups, and individual actions, doctors are working to mitigate the impact of climate change as well as advocating for reductions in carbon emissions. In the future, physicians will be managing the health impacts of climate change, from worsening air quality to frequent heat waves. Medical schools provide a structured space for future physicians to learn about the interaction between human health and climate change. While international efforts to prepare the future health workforce have proceeded at a rapid clip, US medical schools have lagged behind. Medical schools must incorporate environmental health concepts into general curriculum efforts to prepare their graduates to meet the challenges of a changing climate.